Authenticity and the Formation of Culinary Destination Brand Commitment - Lalu Rohadi Rahman; Sitti Mujahida Baharuddin; Fatmasari; Kurniawaty (Advances in Tourism Studies, 2025)
This study examines how perceived authenticity shapes brand equity, emotional attachment, brand loyalty, and brand choice intention in South Sulawesi’s culinary tourism. Although authenticity is widely recognised as a central attribute of gastronomic experiences, the mechanisms through which it influences cognitive, affective, and behavioural outcomes remain insufficiently clarified. This research employs a simplified theoretical model integrating Consumer Based Brand Equity theory and Attachment Theory to explain how authentic culinary encounters generate long term engagement with regional food identities. Data were collected from 214 domestic tourists who had consumed traditional South Sulawesi cuisine within the past twelve months. Partial Least Squares Structural Equation Modeling was used to test the proposed relationships. The findings show that perceived authenticity significantly enhances brand equity, which in turn fosters emotional attachment. Emotional attachment emerges as the strongest predictor of brand loyalty, and loyalty directly drives brand choice intention. The results also reveal direct effects of authenticity on both attachment and loyalty, indicating that authentic experiences can produce immediate affective and behavioural responses independent of cognitive appraisals. These insights contribute to the literature by demonstrating a coherent cognitive to affective to behavioural pathway through which authenticity strengthens culinary destination brands. Practical implications highlight the importance of preserving cultural integrity to support sustainable tourism development.